2020
DOI: 10.1007/s00253-020-10905-4
|View full text |Cite
|
Sign up to set email alerts
|

A tunable l-arabinose-inducible expression plasmid for the acetic acid bacterium Gluconobacter oxydans

Abstract: The acetic acid bacterium (AAB) Gluconobacter oxydans incompletely oxidizes a wide variety of carbohydrates and is therefore used industrially for oxidative biotransformations. For G. oxydans, no system was available that allows regulatable plasmid-based expression. We found that the l-arabinose-inducible PBAD promoter and the transcriptional regulator AraC from Escherichia coli MC4100 performed very well in G. oxydans. The respective pBBR1-based plasmids showed very low basal expression of the reporters β-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 60 publications
(84 reference statements)
3
35
0
Order By: Relevance
“…Three broad-spectrum promoters (P bs1 , P bs2 , and P bs3 ) with different strengths, were generated by random mutation and characterized. In a recent study, a newly tunable L-arabinose-inducible P BAD promoter was discovered to be useful in G. oxydans 621H, and the activity of this promoter was affected by the pH of the medium (Fricke et al, 2020). In summary, the identification of gradient promoters in this study expanded the toolbox of available promoters, and these promoters revealed promising prospects in metabolic engineering of G. oxydans for high-value products.…”
Section: Discussionmentioning
confidence: 75%
“…Three broad-spectrum promoters (P bs1 , P bs2 , and P bs3 ) with different strengths, were generated by random mutation and characterized. In a recent study, a newly tunable L-arabinose-inducible P BAD promoter was discovered to be useful in G. oxydans 621H, and the activity of this promoter was affected by the pH of the medium (Fricke et al, 2020). In summary, the identification of gradient promoters in this study expanded the toolbox of available promoters, and these promoters revealed promising prospects in metabolic engineering of G. oxydans for high-value products.…”
Section: Discussionmentioning
confidence: 75%
“…Until now, an L-arabinose-inducible araC-P araBAD system on the pBBR1MCS-5 backbone is the only regulatable system available for Gluconobacter (Fricke et al 2020). The mechanism of transcriptional gene regulation by AraC is different compared to those of the pure repressor proteins TetR and LacI, which just dissociate from their operator DNA when their respective inducer is bound to the protein.…”
Section: L-arabinose-induced Arac-dependent Regulatable Expressionmentioning
confidence: 99%
“…The L-arabinose concentrations required for highest induction in G. oxydans were much higher than the ones typically used for E. coli. Attempts to increase the arabinose sensitivity of the araC-P araBAD system by expression of the L-arabinose transporter gene araE in tandem with araC from the promoter of araC had a strong negative effect on the growth of G. oxydans and the expression performance (Fricke et al 2020). With a pBBR1MCS-5 derivative carrying araE separately under control of the weak constitutive G. oxydans promoter P GOX0384 no G. oxydans 621H transformants could be obtained yet, suggesting a severe growth defect upon araE expression in G. oxydans, even in the absence of L-arabinose (our unpublished results).…”
Section: L-arabinose-induced Arac-dependent Regulatable Expressionmentioning
confidence: 99%
See 2 more Smart Citations